Hukum antar waktu (HAW) dalam UU No. 5 Tahun 1986 dan UU No. 30 tahun 2014 - Firzhal Arzhi Jiwantara (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
Inter-Time Law in Law Number 30 of 2014 concerning Government Administration (UUAP) related to the content of the transfer of authority to adjudicate Government Administration disputes, the length of the period for making rules for implementing the Law and the imposition of the provisions of Article 1 number 9 of Law Number 51 of 2009 concerning the Second Amendment to Law Number 5 of 1986 concerning the State Administrative Court and how does the law of time explain that. The purpose of this study is to find out the law between times in Law Number: 30 of 2014 concerning Government Administration. In this research using normative legal research methods with a statute approach, and a conceptual approach (conseptual approach). The results of the research are the inter-time law in Law Number 30 of 2014 concerning Government Administration regarding transitional provisions regulated by 3 (three) Articles, namely Article 85 paragraph (1) and paragraph (2) of the content material related to the transfer of authority to adjudicate Government Administration disputes, Article 86 content material regarding the duration of the period of making rules for implementing the Law, and Article 87 content material related to the meaning of the provisions of Article 1 number 9 Law Number 51 of 2009 concerning the Second Amendment to Law Number 5 of 1986 concerning the State Administrative Court.